2007
DOI: 10.1007/s10455-007-9095-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability of area-preserving variations in space forms

Abstract: In this article, we deal with compact hypersurfaces without boundary immersed in space forms with S r+1 S 1 = constant. They are critical points for an area-preserving variational problem. We show that they are r -stable if and only if they are totally umbilical hypersurfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Volume preserving variational problem is an important theme into the theory of isometric immersion and has been studied by many authors (see, for instance, references [1] to [5,7,12]). It is well known that immersions with constant mean curvature are critical points for the variational problem of minimizing the area functional keeping the balance of volume zero.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Volume preserving variational problem is an important theme into the theory of isometric immersion and has been studied by many authors (see, for instance, references [1] to [5,7,12]). It is well known that immersions with constant mean curvature are critical points for the variational problem of minimizing the area functional keeping the balance of volume zero.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…In this setting, we establish a similar result to Proposition 5.1 of [9] and Proposition 5.3 of [16]. Next, for nonnegative real numbers a 0 and a 1 (with at least one nonzero),…”
Section: Strongly Stable Linear Weingarten Hypersurfaces In H N+1mentioning
confidence: 66%
“…They showed that such hypersurfaces are r-stable if, and only if, they are geodesic spheres; thus generalizing the previous results on constant mean curvature closed hypersurfaces. Later on, He and Li [16] treated the case of compact hypersurfaces without boundary immersed in space forms with the quotient H r+1 /H constant, for some 1 ≤ r ≤ n − 1. They proved that such hypersurfaces are r-stable if, and only if, they are totally umbilical.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of hypersurfaces for volume preserving variational problem has a long history since the first result for the stability of constant mean curvature in the Euclidean space by Barbosa and do Carmo [3]. Many authors have been interested in stability problems in various contexts, like for other space forms and/or higher order mean curvatures (see [1,2,4,5,7,8,9,10,12] for instance). In 2013, Velásquez, de Sousa and de Lima [21] defined the notion of (r, s)-stability which generalizes the classical notion of stability for the mean curvature or r-stability for higher order mean curvatures.…”
Section: Introductionmentioning
confidence: 99%